2023
DOI: 10.1038/s41390-023-02827-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hemodynamic effects of chest compression delivered via machine or human in asphyxiated piglets

Megan O’Reilly,
Tze-Fun Lee,
Po-Yin Cheung
et al.

Abstract: Background High-quality chest compressions (CC) are an important factor of neonatal resuscitation. Mechanical CC devices may provide superior CC delivery and improve resuscitation outcomes. We aimed to compare the hemodynamic effects of CC delivered by machine and human using a neonatal piglet model. Methods Twelve asphyxiated piglets were randomized to receive CC during resuscitation using an automated mechanical CC device (“machine”) or the two-thumb enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Endotracheal or intramuscular epinephrine is not associated with any significant hemodynamic improvement during chest compressions, possibly due to poor bioavailability [32,33]. O'Reilly et al have shown increased stroke volume, but no improvement in diastolic pressure during chest compressions using a mechanical device [34]. Administering a normal saline bolus can potentially increase the diastolic pressure, but requires umbilical venous catheterization and intraosseous line placement and may be associated with pulmonary edema [35].…”
Section: Discussionmentioning
confidence: 99%
“…Endotracheal or intramuscular epinephrine is not associated with any significant hemodynamic improvement during chest compressions, possibly due to poor bioavailability [32,33]. O'Reilly et al have shown increased stroke volume, but no improvement in diastolic pressure during chest compressions using a mechanical device [34]. Administering a normal saline bolus can potentially increase the diastolic pressure, but requires umbilical venous catheterization and intraosseous line placement and may be associated with pulmonary edema [35].…”
Section: Discussionmentioning
confidence: 99%